Does resveratrol affect prepared sperm parameters and chromatin quality in normozoospermic and asthenozoospermic patients before and after freezing? A lab trial study - Masoomeh Mohammadzadeh; Mohammad Ali khalili; Vahid Ramezani; Hamed Hamishehkar; Marvast Laleh Dehghan; Esmat Mangoli; Mahya Rajabi; Zhima Akhavan Sales; Ali Reza Talebi (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Previous studies have examined the effect of resveratrol as a potent antioxidant for free radicals in semen. While, the prepared spermatozoa are more affected by ROS factors due to centrifugation and incubation. Objective: To evaluate the RSV's effects on the prepared sperm parameters and chromatin quality in both normozoospermic and asthenozoospermic cases before and after freezing. Materials and Methods: The sample of 10 normozoospermic and asthenozoospermic men was prepared through the swim-up method. The groups were then divided into two samples of control and experimental (exposure to 30 µmol/l of RSV) to evaluate and compare the sperm parameters and chromatin quality before and after freezing. Results: The motility and viability of spermatozoa were seen to be significantly different before and after freezing separately in the control and treatment samples of the groups (p ≤ 0.001 and p = 0.001, respectively). However, the stated difference between the control and treatment samples of normozoospermic and asthenozoospermic patients were not significant (p > 0.05). In addition, the sperm morphology and chromatin quality were not significantly different between the two samples of each group; nonetheless, chromatin quality of the treated sample was better than that of the control before and after freezing. Conclusion: Despite the protective effects of RSV on the semen samples, RSV cannot affect significantly the prepared sperms parameters and chromatin quality in normozoospermic and asthenozoospermic patients.Key words: Resveratrol, Chromatin, Motility, Spermatozoa, Freeze.